Hypomagnesemia: a Potential Underlooked Cause of Persistent Vitamin D Deficiency in Chronic Kidney Disease - Matias, P (2023)
Magnesium and vitamin D play important roles in most cells of the body. These nutrients act in a coordinated fashion to maintain physiologic functions of various organs, and their abnormal balance could adversely affect these functions. Therefore, deficient states of both nutrients may lead to several chronic medical conditions and increased cardiovascular and all-cause mortality. Chronic kidney disease (CKD) patients have altered metabolism of both magnesium and vitamin D. Some studies indicate that magnesium could have a role in the synthesis and metabolism of vitamin D, and that magnesium supplementation substantially reversed the resistance to vitamin D treatment in some clinical situations. Recent observational studies also found that magnesium intake significantly interacted with vitamin D status and, particularly with the risk of cardiovascular mortality. It is therefore essential to ensure adequate levels of magnesium to obtain the optimal benefits of vitamin D supplementation in CKD patients. In this review, we discuss magnesium physiology, magnesium and vitamin D metabolism in CKD, potential metabolic interactions between magnesium and vitamin D and its clinical relevance, as well as the possible role of magnesium supplementation to assure adequate vitamin D levels.